Conversion of food waste to energy: A focus on sustainability and life cycle assessment. (15th October 2021) - Sridhar, Adithya; Kapoor, Ashish; Senthil Kumar, Ponnusamy; Ponnuchamy, Muthamilselvi; Balasubramanian, Sivasamy; Prabhakar, Sivaraman
Graphical abstract: Highlights: Current food waste to energy conversion technologies lack in terms of efficiency and economic feasibility. The sustainable approach for converting food waste into value-added products is discussed. Life cycle assessment is a preferable option for evaluating environmental impacts and decision making. Circular bioeconomy models could be explored for efficient utilization of wastes. Abstract: Rapid industrialization and population growth have resulted in the wastage of significant quantity of food globally throughout the value chain right from harvesting to storage, processing and consumption. Normally, these waste materials are allowed to decay in the natural process or burnt to recover a part of the energy in the thermal form, leading to environmental pollution and loss of value. There is an imperative need to realize that food waste is a bundle of energy, which requires carefully planned recovery without damaging the environment. Conversion of food waste to bio-based liquid or gaseous fuels appears to be an attractive option to meet the escalating demand for fuel and at the same time slowing down the fast-depleting fossil fuel resources. In this context, it is felt appropriate to review the current status of the available technologies which are used in the disposal of food waste in order to identify the variables for process intensification to convert them to fuel keeping in mind the environmental concerns and logistics of utilization. The technologies including incineration, landfill, composting, anaerobic digestion, pyrolysis and biochemical methods have been assessed alongside the recent developing technologies such as hydrothermal carbonization and supercritical water gasification. The critical evaluations of these technologies have been made based on the concepts of life cycle analysis, multi-objective optimization and circular bio-economics which help in assessing the environmental impact. Finally, safety aspects and the way forward are highlighted for future work. This article could form a promising path towards a holistic assessment of efficient food waste to energy conversion for a sustainable development.